2008
DOI: 10.3846/1392-3730.2008.14.23
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Corrosion Protection for Reinforced Concrete Structures With Surface Coatings/Gelžbetoninių Konstrukcijų Su Paviršinėmis Dangomis Korozinės Apsaugos Modeliavimas

Abstract: Abstract. Corrosion is a serious problem for the durability of reinforced concrete structures. These structures need to be protected from corrosion in a variety of exposure conditions ranging from atmospheric to continuous immersion in water or chemicals. One of the ways to protect reinforced concrete structures from corrosion is to use protective coatings. The surface barriers of non-degradable materials are able to slow down considerably the rate of deterioration of concrete structures and to overcome most d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In this situation the system behaviour can be represented by Markov model which is probably the most used to simulate the different stochastic processes of complex systems. Although it is possible to predict deterioration of CPS with other forms of models, including also deterministic models (Kamaitis 2008), the Markovian model is particularly suitable for condition state assessments based on inspection cycles. It requires only limited inspection data before model estimation becomes possible.…”
Section: Fig 2 States Of Safe Operation Of Cpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation the system behaviour can be represented by Markov model which is probably the most used to simulate the different stochastic processes of complex systems. Although it is possible to predict deterioration of CPS with other forms of models, including also deterministic models (Kamaitis 2008), the Markovian model is particularly suitable for condition state assessments based on inspection cycles. It requires only limited inspection data before model estimation becomes possible.…”
Section: Fig 2 States Of Safe Operation Of Cpsmentioning
confidence: 99%
“…In the author's paper (Kamaitis 2008) the concept of corrosive protection system (CPS) of reinforced concrete members taking into account the performance of protective surface barrier, concrete cover and steel reinforcement itself was proposed. Degradation of CPS as multicomponent protection system begins, in general, from the top layer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Kamaitis (2007b) recommended the use of polymer protective coatings onto concrete surfaces where special protection against aggressive attack is necessary and demonstrated that polymer coatings can protect concrete from a variety of aggressive chemicals; his proposed models can be efficiently applied to assess the service life and performance of polymer protective coatings under different chemical exposure conditions. Kamaitis (2008) also took into account protective surface coating, concrete cover, and steel reinforcement in a whole to study the corrosion protection and service life of reinforced concrete structures. Recently, Yoon (2012) studied the effect of coating on chloride penetration through cracks in high-strength concrete with and without steel fibres; he concluded that coating can substantially reduce the chloride penetration into concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the atmosphere on reinforced concrete structures causes the carbonation of concrete (Kamaitis 2008). As a result of this process, a reduction in the concrete cover protective properties occurs, along with an increased corrosion hazard for the reinforcement.…”
Section: Introductionmentioning
confidence: 99%